Study of academic performance in medical students at the time of COVID-19 pandemic - Amatya, Neebha; Prajapati, Rajesh; Magar, Rajab Rana; Shrestha, Ripti (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: The world has faced a disastrous period at the time of the pandemic of corona virus- 19. The education system was hampered along with all the sectors of life and therefore, it was realized that a switch from the conventional way of teaching to online teaching is needed. The current study was done to analyze the impact of the COVID-19 lockdown on the academic performance of medical students at Gandaki medical college of Pokhara, Nepal.Methods: It was a descriptive study of the first and second-year medical students of Gandaki Medical College. The Likert scale was used to measure the effect of the COVID-19 lockdown on academic performance and to evaluate online education. A census sampling technique was used to collect the data.Results: A total of 171 participants answered the questionnaire with a response rate of 87%. The data showed that covid-19 lockdown affected the academic performance of most participants of 98.2% with varying degrees. The mean evaluation score for online theory education was 4.7±2.06 while for the practical lessons was 2.06±1.4.Conclusions: COVID-19 pandemic lockdown affected the academic performance of most participants to varying degrees. The academic performance of medical students with the online teaching method is effective during COVID-19 lockdown.